Comparative analysis of the nineteenth century Austrian Empire maps applied to the protection and restoration of designed landscapes. Issue 3 (3rd July 2022) - Baster, Przemysław
Abstract: The Second Military Survey and the Austrian Cadastre are two of the most important maps of Austrian Empire for landscape analyses. They show the territories encompassing twelve current European countries; both were created around the same time in nineteenth century, but each of them presents different detailed data concerning historical gardens and designed landscapes. Their comparative analysis allows to reconstruct brilliant spatial solutions and elements, which currently do not exist or are hard to perceive. The research concerning both famous garden estates and the villages near Krakow proves that such studies of the Austrian Empire maps are necessary to be applied to the landscape designing and spatial development. They make it possible to adapt historical forms to today`s needs, design appropriate spatial solutions, protect cultural heritage or even to restore non-existent elements of historical gardens and designed landscapes.